Sądy specjalnej jurysdykcji w Stanach Zjednoczonych Ameryki - Kralka, Bartosz (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2019)
The article deals with issues related to the historical division of federal courts in the United States into constitutional courts and courts of the legislature. In his work, the author tries to present the process of creating judgments of laws and they are equating with constitutional courts. The article presents the attitude of the US Supreme Court to the position of the legislative courts and their judges.
Keywords: special courts; federal courts; Article III courts; USA judicial system